Detecção precoce do câncer de mama: conhecimento, atitude e prática de mulheres com história familiar - Almeida, Adrielle Oliveira Azevedo de (2021)
The risk of hereditary breast cancer makes it necessary to identify first-degree relatives of women diagnosed with breast cancer and approach them about early detection methods in order to know their adherence to these methods. Assessing the knowledge, attitude and practice of first-degree relatives of women with breast cancer about early detection exams (clinical breast examination and mammography) will allow for the most appropriate nursing treatment for the early detection of breast cancer. Thus, the objective was to assess the knowledge, attitude and first-degree practice of women diagnosed with breast cancer about early detection tests. This is a cross-sectional study using the Knowledge, Attitude and Practice (KAP) survey, carried out in a public hospital with reference to breast cancer, whose sample consisted of 100 women over 18 years of age, with first-degree kinship of women with breast cancer, who accompanied their family member during the collection period, in the months between April 2019 and March 2020. The age of the participants ranged from 19 to 69 years, with a mean age of 41 years. The attitude of the participants proved to be adequate (76%), but the majority had inadequate knowledge (73%) and practice (70%), regarding early detection tests. Statistical significance was found for age with inadequate knowledge and practice among younger participants, under 40 years of age; inadequate knowledge and practice among those who became pregnant; from age of first pregnancy and breastfeeding to inadequate practice among those who became pregnant before 30 years of age; hormone replacement for inadequate knowledge and practice; benign disease to inadequate practice; and the kinship to inadequate knowledge. Given the above, it is concluded that having a first-degree relative with breast cancer can influence the level of perception of the importance of early detection tests, but it does not mean having better knowledge and greater adherence to the tests. The use of the CAP methodology made it possible to know the first-degree relatives of women with breast cancer in the face of tests that help in the early detection of the disease. However, it is necessary to expand the role of health promotion aimed at the family context, in mobilizing adherence to tests for early detection of breast cancer, according to the needs of these women with a family history.